Data Journalism as specialization of Internet news organizations - Flores Vivar, Jesús (2013)
This work relates to the analysis of a form of specialization based on Data Journalism and news organizations (old Media companies) have been incorporating this specialty as innovation journalism. Data Journalism involves using statistical and visualization tools to create and tell stories better in new and attractive to the Internet audience. It is the evolution of what some years ago was known as Precision Journalism or Desktop Journalism.